PERKEMBANGAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL - Rohimah; Ubabuddin (CV. Adiba Aisha Amira, 2026)
Indonesia is a country rich in ethnicities, customs, religions and cultures. This wealth is a source of pride if it is managed well, but on the other hand, differences can easily lead to friction that can cause prolonged hostility. Multicultural education is one of the efforts to instil a character of peace and inclusiveness towards every difference. Multicultural Islamic education is education that places multiculturalism as one of its educational visions with the main characteristics of being inclusive, egalitarian, democratic, and humanistic, while remaining firm in its spiritual values and beliefs based on the Qur'an and hadith. Thus, the core or substance of multicultural Islamic education is the willingness to accept other people or groups equally as a whole, regardless of differences in culture, ethnicity, gender, language, religion, and so on. Multicultural education is the answer to instilling multicultural values in students in order to create harmony, tolerance, and mutual respect in a diverse society.